Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan pada Perusahaan yang Terdaftar di BEI Terindeks LQ45 Periode 2022-2024 - Rahayu, Nika Esti; Primasiwi, Asri; Ibrahim, Rosida (-, 2025)
This research aims to analyze the effect of profitability and leverage on company value in companies listed on the LQ45 index of the Indonesia Stock Exchange during the 2022-2024 period. The research sample consisted of 33 companies that met the criteria, with secondary data in the form of annual financial reports. The variables used include profitability measured through the Return on Assets (ROA) ratio, leverage through the debt to shareholder equity ratio, and company value using Price Book Value (PBV). The analytical method applied is panel data regression analysis. The research results show that partial profitability and leverage do not have a significant effect on company value. These findings support the theory that in large and stable companies such as those indexed in LQ45, traditional financial factors are no longer the primary determinant of company value. In contrast, external factors and innovation strategies can have a greater influence.